Peritraumatic tonic immobility is associated with PTSD symptom severity in Brazilian police officers: a prospective study - Maia,Deborah B. (2015)
Objective: Peritraumatic reactions feature prominently among the main predictors for development of posttraumatic stress disorder (PTSD). Peritraumatic tonic immobility (PTI), a less investigated but equally important type of peritraumatic response, has been recently attracting the attention of researchers and clinicians for its close association with traumatic reactions and PTSD. Our objective was to investigate the role of PTI, peritraumatic panic, and dissociation as predictors of PTSD symptoms in a cohort of police recruits (n=132). Methods: Participants were asked to complete the following questionnaires during academy training and after the first year of work: Posttraumatic Stress Disorder Checklist - Civilian Version (PCL-C), Physical Reactions Subscale (PRS), Peritraumatic Dissociative Experiences Questionnaire (PDEQ), Tonic Immobility Scale (TIS), and Critical Incident History Questionnaire. Results: Employing a zero-inflated negative binomial regression model, we found that each additional point in the TIS was associated with a 9% increment in PCL-C mean scores (RM = 1.09), whereas for PRS, the increment was 7% (RM = 1.07). As the severity of peritraumatic dissociation increased one point in the PDEQ, the chance of having at least one symptom in the PCL-C increased 22% (OR = 1.22). Conclusions: Our findings highlight the need to expand investigation on the incidence and impact of PTI on the mental health of police officers.